Soil P Diffusion and Availability Modified by Controlled-Release P Fertilizers - Volf, Marcelo R.; Rosolem, Ciro A. [UNESP] (Springer, 2020)
Slow-release fertilizers have been proposed as tools to increase P fertilizer use efficiency in tropical acidic soils with high P adsorption, low P availability, and mobility. However, results have been controversial since soil diversity and the fertilizer itself may influence the results, which is not completely understood. Soil P diffusion and availability were studied in soils with different P fertilization histories, where triple superphosphate (TSP) and single superphosphate (SSP) coated with a polymer or with humic acid and complexed with humic acid were applied under laboratory conditions. No difference in soil P availability and diffusion was observed between humic acid-complexed, polymer, and humic acid-coated TSP and conventional TSP. For SSP, soil P availability was 15 to 30% lower in the region of application for the polymer and 0 to 16% for the humic-coated fertilizer. For the polymer-coated SSP, P diffusion was lower in some soils. With both base fertilizers, the soil adsorption capacity was more determinant of P diffusion than the protection of the fertilizers. Coating P fertilizers with polymer and complexing or coating the fertilizer with humic acid does not increase P availability or diffusivity in soil since these processes are driven mainly by the soil characteristics. Therefore, the potential of these controlled-release P fertilizers in increasing P use efficiency is low.
Keywords: Phosphate fertilizer; Slow release; P adsorption; Polymer; Humic acid